COMPARATIVE CHARACTERISTICS OF BIOMATERIALS FOR THE REPLACEMENT OF JAW BONE DEFECTS AND THEIR ROLE IN THE PREVENTION OF INFLAMMATORY COMPLICATIONS - V.M. Havryliev; A.V. Kopchak; N.B. Kuzniak; D.V. Steblovski; O.A. Toropov; P.I. Yatsenko (Український стоматологічний альманах)
In contemporary clinical practice, biomaterials are considered a promising alternative to traditional bone grafts due to their potentially unlimited availability, bioinertness, and reduced likelihood of developing inflammatory complications. At the same time, the implementation of tissue engineering methods in clinical practice remains limited by a number of barriers. Current approaches aim to create conditions for functional bone tissue regeneration through the synergy of biomaterials, cellular technologies, and factor-based therapy.